CANCER URINARY BLADDER 5 YEAR EXPERIENCE AT CENAR, QUETTA - ULLAH, ROOH; NUSRAT, J; HAMDAN, SRH I; Burdy, CM; Khurshid, A (Journal of Ayub Medical College Abbottabad, 2001)
Background: Purpose of this study was to sec the incidence, age. sex. ideographical distribution, symptoms, personal habits, signs, histo-pathology. early diagnosis and management of cases of Cancer Urinary Bladder (Ca IB) in the patients coming to CTNAR. Quetta. Pakistan Methods: A retrospective study was conducted at Cl VAR for a period of 5 years from I’1 Jan 1993 to 3I-1 Dec. 97. In which about 100 cases of cancer of urinary bladder were included, out of which 82 patients were male and 12 were females. Results: During our 5-year period of study. 3571 new cases of cancer were registered at CENAR, out of which 100 (2 8% of total No. of cases) were of Ca UB. Hence 20 new cases of Cl UB per year were registered at CTNAR I he maximum number of cases was registered in 1996 Conclusion: Our study concluded that Ca UB occurs more in male with a male female ratio of 4.5 I and a high incidence after 40 years of age. No patient below 20 was reported. Histopathologically. Transitional Cell Carcinoma was dominating (75%). Other histological types seen were squamous cell carcinoma 14%). Adenocarcinoma 13%). UD (5%) and HPNA (10%) A considerable number of patients were using different preparations of tobacco (cigarette smoking (6%). Hubble-Bubble (5%) and Niswar (Snuff) (12%). The patients were mainly treated with Radiotherapy, because at the time of reporting they were already in stage II or beyond (97%). Some patients were also treated by surgery such as TUR. partial or radical cystectomy. A few patients (6%) also received chemotherapy.